The mediating effect of parental involvement on school climate and continuous improvement - Pourrajab, Masoumeh; Ghani, Muhammad Faizal A.; Panahi, Akbar (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2018)
This study attempted to investigate the mediating effect of parental involvement on the relationship between school climate and continuous improvement. To achieve this aim, the researchers conducted a descriptive research with quantitative approach to explore this mediating effect. The population of this study was 42870 Grade 1 and 2 high school students in Lorestan state, Iran. With applied simple and stratified random sampling, a total of 400 students were chosen as the participants in this study. The researchers used questionnaire as an instrument to collect the data. The results of this study illustrated the medium level for parental involvement, school climate and continuous improvement, based on students’ perception. In addition, the findings show the mediating effect of parental involvement on the relationship between school climate and continuous improvement. These results have suggested that if school climate and parental involvement are improved, it could be an effective strategy to increase continuous school improvement. The results of this research proposed more comprehensive empirical view on how parental involvement can improve the relationship between school climate and continuous improvement in Iranian education system.